ChemInform Abstract: A Protocol for Amide Bond Formation with Electron Deficient Amines and Sterically Hindered Substrates. Issue 20 (April 2016) - Due‐Hansen, Maria E.; Pandey, Sunil K.; Christiansen, Elisabeth; Andersen, Rikke; Hansen, Steffen V. F.; Ulven, Trond
Abstract: A method for efficient in situ coupling of sterically hindered carboxylic acids with hindered or electron deficient amines and oxazolidinones is developed.